Improving the Allocative Efficiency of the HIV Response Across the HIV Testing and Treatment Cascade in Zimbabwe : Findings from an Optima HIV Modelling Analysis - World Bank (World Bank, Washington, DC, 2020)
In an effort to improve the efficiency of the HIV response in Zimbabwe, the World Bank in collaboration with the Government of Zimbabwe and the Burnet Institute conducted a mathematical modelling analysis using the Optima HIV mathematical model (http://optimamodel.com/hiv) to: 1) provide national and provincial HIV acquisition and transmission estimates and patterns from 2000 to 2017 and predict future trends to 2030 (Phase 1) and 2) identify opportunities for optimizing resource allocation across the HIV treatment cascade through different implementation options for HIV testing and treatment services (differentiated HIV care) (Phase 2). This policy brief provides a summary of the key findings and policy recommendations from this study. The full phase 1 and phase 2 reports can be accessed at [http://hdl.handle.net/10986/33270] and [http://hdl.handle.net/10986/33271].